Strong grain neighbour effects in polycrystals - Abdolvand, H; Wright, J; Wilkinson, A (Springer Nature, 2018)
Anisotropy in single crystal properties of polycrystals controls both the overall response of the aggregates and patterning of local stress/strain distributions, the extremes of which govern failure processes. Improving the understanding of grain-grain interactions has important consequences for in-service performance limits. Three-dimensional synchrotron X-ray diffraction was used to study the evolution of grain resolved stresses over many contiguous grains in Zr and Ti polycrystals deformed in situ. In a significant fraction of grains the stress along the loading axis was found to decrease during tensile plastic flow just beyond the macroscopic yield point; this is in the absence of deformation twinning and is a surprising behaviour. It is shown that this phenomenon is controlled by the crystallographic orientation of the grain and its immediate neighbours, particularly those adjacent along the loading axis.